1998
DOI: 10.1175/1520-0485(1998)028<2019:emfiiz>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Eddy–Mean Flow Interaction in Zonal Oceanic Jet Flow along Zonal Ridge Topography

Abstract: Motivated by satellite altimeter observations of enhanced sea level variability near steep topographic slopes in the Southern Ocean, effects of topography on the spatial distribution of mesoscale eddies and on eddy-mean flow interaction are investigated using a two-layer, wind-forced, quasigeostrophic channel model. The principal topography, a zonal ridge with a zonal modulation of ridge height and width, is an idealized version of a segment of the Southeast Indian Ridge along the path of the Antarctic Circump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Still, QG has historically proven to be an important test bed for understanding how coherent structures determine the structure and statistical properties of turbulent geophysical flows. In particular, this study builds on modeling work by Witter and Chelton (1998) and Bracco and Pedlosky (2003) in which topography impacts the flow through the modification of potential vorticity gradients that feed back on linear instability and nonlinear turbulent properties of the flow. This paper focuses on simulations where topography catalyzes a reorganization of the front structure.…”
Section: Jet Transitions In An Idealized Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, QG has historically proven to be an important test bed for understanding how coherent structures determine the structure and statistical properties of turbulent geophysical flows. In particular, this study builds on modeling work by Witter and Chelton (1998) and Bracco and Pedlosky (2003) in which topography impacts the flow through the modification of potential vorticity gradients that feed back on linear instability and nonlinear turbulent properties of the flow. This paper focuses on simulations where topography catalyzes a reorganization of the front structure.…”
Section: Jet Transitions In An Idealized Modelmentioning
confidence: 99%
“…Of particular interest are regimes in which changes in bottom topography lead to a large-scale reorganization of the jet structure along the channel. This model builds on the work of Witter and Chelton (1998), who considered eddy-mean flow interactions within a QG channel with zonally varying topography. However, their domain permitted a single circumpolar jet.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., Gill et al 1974;Pedlosky 1987;Spall 2000;Vallis 2006). Energy from the time-varying flow can also be transferred back to the time-mean circulation through a variety of processes including rectification and topographic steering (e.g., Whitehead 1975;McWilliams et al 1978;Marshall 1984;Johnson et al 1992;Witter and Chelton 1998); similar phenomena are found in atmospheric jet streams (e.g., Williams et al 2007). At the same time, energy can also be redistributed among different spatial scales/vertical modes through energy cascades (e.g., Salmon 1978;Fu and Flierl 1980;Scott and Wang 2005) and be transmitted over large distances through, for example, advection or the propagation of rings and waves.…”
Section: Introductionmentioning
confidence: 99%
“…Energy from the time-varying flow can also be transferred back to the time-mean circulation through a variety of processes including rectification and topography steering (e.g. Whitehead, 1975;McWilliams et al, 1978;Marshall, 1984;Johnson et al, 1992;Witter and Chelton, 1998); similar phenomena are found in atmospheric jet streams (e.g. Williams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%